PENGARUH HABITAT KOMPLEKS TERHADAP KOMPOSISI KOMUNITAS MAKROINVETEBRATA DALAM SEBUAH KOLAM AIR TAWAR YANG BERSTATUS DYSTROPHIC - Tjokrokusumo, Sabaruddin Wagiman (Jurnal Hidrosfir Indonesia, 2006)
A study of the role of habitat complexity and predation on the composition ofthe macroinvertebrate community in a small dystrophic wetland wasundertaken using artificial substrates. Rectangular samplers of increasingcomplexity were constructed from nylon mesh and wooden dowelling.Samplers of three levels of complexity were developed in both caged anduncaged forms to evaluate the effects of substrate complexity and predationon macroinvertebrate richness and abundance. A total of 24 samplers (6treatments x 4 relicates were deployed in swamp for 8 weeks in September/November 1995. The results indicated that increased habitat complexity doeslead to species richness, but cages have an effect in addition to layers aspreferred habitat for both prey and predator. Increasing richness is not followedby an increase in abundance in more complex habitats. However, an increasein habitat complexity tended to result in a decrease in abundance, probablydue to predation with the lowest abundance found at intermediate compexity.